Growth hormone receptor isoforms and fracture risk in adult‐onset growth hormone‐deficient patients. (22nd August 2016) - Mormando, M.; Chiloiro, S.; Bianchi, A.; Giampietro, A.; Angelini, F.; Tartaglione, L.; Nasto, L.; Milardi, D.; Formenti, A.M.; Giustina, A.; De Marinis, L.
Summary: Introduction: Growth hormone deficiency is considered the most important factor determining skeletal fragility in hypopituitary patients. Osteoblasts and chondrocytes express growth hormone (GH) receptor. Two GH receptor isoforms (GHRi) have been identified: they differ for the presence/absence of a protein fragment encoded by exon 3 of GHR gene. Consequently, three genotypes were identified: carriers of both the full‐length proteins ( flfl‐GHR ), carriers of one full‐length protein and one deleted protein ( fld3‐GHR ) and carriers of both deleted proteins ( d3d3‐GHR ). This polymorphism confer s a higher sensitivity to endogenous GH and to recombinant human GH (rhGH); its effect on bone metabolism and skeletal fragility is unknown. The aim of this article was to investigate the role of GHRi in predicting skeletal fragility in adult‐onset GHD (AO‐GHD) patients. Subjects and methods: A cross‐sectional study was conducted to investigate the association between the d3‐GHR isoform and the prevalence of morphometric vertebral fractures (VFs) in AO‐GHD. Ninety‐three AO‐GHD were enrolled. Forty‐nine patients carried flfl‐GHRi (52·7%), and 44 patients (47·3%) carried at least one allele of the d3‐GHR isoform. Thirty‐two VFs were documented. Fifty‐seven patients underwent rhGH replacement therapy. Results: Median age was significantly higher in fractured patients as compared to nonfractured ones; d3‐ carrier patients showed a lower VF risk as compared to flfl ‐GHRi (OR: 0·37, 95% IC: 0·24–0·55, P < 0·0001). This finding was also confirmed in AO‐GHD undergoing rhGH replacement therapy. Conclusion: This study suggests that d3‐GHR may protect AO‐GHD particularly when treated with rhGH from the risk of VFs.